Sosialisasi Optimalisasi Potensi Modal Sosial Disabilitas: Penguatan Kolaborasi Stakeholder untuk Pendidikan Inklusif yang Berkualitas - Laelia Nurpratiwiningsih; Sesya Dias Mumpuni; Ike Desi Florina; Sri Adi Nurhayati; Hijrah Eko Putro (Jurnal Pemberdayaan Masyarakat, 2024)
Optimizing the potential of social capital in the context of disability is a crucial aspect in realizing quality inclusive education and requires active collaboration between various related parties in creating a learning environment for disabilities. Social capital is defined as a network of social relationships, norms and values ​​that facilitate cooperation between individuals and groups. This activity aims to explore how stakeholder collaboration can be improved through optimizing the potential of social capital to support quality inclusive education for individuals with disabilities. The methods used are material selection, introduction and training objectives, supporting skills development sessions, case studies and group discussions, evaluation and feedback. The results show that effective stakeholder collaboration in supporting inclusive education requires a deep understanding of the potential and barriers faced by individuals with disabilities. The potential for social capital, such as: trust, interdependence, and a strong network of relationships between stakeholders is key in building an inclusive educational environment. Strategies to optimize the potential of social capital include: training and capacitation of stakeholders about the importance of inclusion and social capital, establishing joint discussion forums between stakeholders, and implementing policies that support inclusive education. The active role and commitment of social capital from all parties involved is very necessary to create an inclusive, fair and quality educational environment for all individuals.